Gender and regional differences in body image dissatisfaction in modern university students : a pilot study in two cities of Eastern Europe - Godina, Elena (Array, 2020)
Complex anthropological and psychological study of the university students was carried out in two regions (the cities of Moscow and Tiraspol) with the aim to reveal gender and regional differences of body image dissatisfaction and their connection with the body build. 502 individuals (187 males and 315 females) aged from 17 to 25 years were investigated. The program included anthropometric measurements (height and weight, with further calculation of Body Mass Index – BMI), evaluation of body mass components, as well as psychological testing with Stunkard’s silhouette scale and the Situational Inventory of Body-Image Dysphoria (SIBID). It was found that among the representatives of both sexes the level of dissatisfaction with their own body is relatively similar (69% of males and 67% of females). However the girls were mostly dissatisfied with their excessive, as they perceived, body mass (83% of the total number of dissatisfied individuals) while the boys were dissatisfied mostly because of their underweight (60% of the total number of dissatisfied individuals). Besides, the girls were more likely to exaggerate their weight while the boys perceived it as smaller than it really was. In girls certain social influences had more impact on body image dissatisfaction than in boys. Among the girls studied, the Muscovites were more critical to their own physical appearance, which resulted in lower self-assessment of their body image and, consequently, in less positive influence of this assessment on the quality of life compared to the girls from Tiraspol.